Origem e distribuição das artérias da coxa e da perna de javali (Sus scrofa LINNAEUS, 1758) - Pfrimer, Gabriel de Abreu (2018)
The aim of this study was to study the distribution of the arteries of the thigh and the boar leg (Sus scrofa LINNAEUS, 1758). Twenty-five animals of varying generations from donations were used. The arterial system of each animal was marked with a 50% latex stained with specific red pigment. Binding of the animals was achieved by intramuscular, subcutaneous and intracavitary injections of aqueous 10% formaldehyde solution. The external iliac artery emitted the body of the last two lumbar vertebrae, a deep femoral artery that had its direction between the medial faces of the vastus medialis and pectineum muscles. The deep femoral artery branched into the proximal third of the pelvic limb in the pudendoepigastric trunk and medial circumflex artery of the femur. In 10% of the cases, the cases did not occur in relation to culture of the pudendal and caudal epigastric arteries. The femoral artery was the distal segment of the external iliac artery in the thigh, a lateral circumflex artery was emitted from the femur in the proximal third of the limb and branched into two branches, ascending and descending, distributing in the vastus medialis and rectus muscle of the thigh. No middle third of the medial aspect of the thigh was observed the saphenous artery. The distal portion of the thigh, the caudal femoral artery is distributed by one ascending and the other descending. The popliteal artery was a continuation of femoral art when crossing a pop fossa in the leg. When a medial head of the gastrocnemius muscle was passed, a cranial tibial artery and a caudal tibial artery were emitted. Before reaching the head of the gastrocnemius muscle, a popliteal artery emits a lateral artery of the knee, medial artery of the knee, lateral distal artery of the knee and a medial artery of the knee. In the proximal third of the leg, a cranial cranial perforating the interosseous membrane of the leg bone and a lateral skull of the leg, gave rise to a recurrent tibial cranial technique and continued its mission to a distal region of the leg. The caudal tibial artery prior to its movement is a trifurcation and its branches distribute through the gastrocnemius, soleus, popliteal, flexor digitorum, and flexor digitorum muscles.